2022
DOI: 10.1016/j.mayocp.2021.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cardiovascular Disease Risk Factors With Sociodemographic Characteristics and Health Beliefs Among a Community-Based Sample of African American Adults in Minnesota

Abstract: Objective: To assess cardiovascular disease (CVD) and CVD risk factors and their association with sociodemographic characteristics and health beliefs among African American (AA) adults in Minnesota. Methods: A cross-sectional analysis was conducted of a community-based sample of AA adults enrolled in the Minnesota Heart Health Program Ask About Aspirin study from May 2019 to September 2019. Sociodemographic characteristics, health beliefs, and self-reported CVD and CVD risk factors were collected. Prevalence r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…These patterns may be a result of the higher burden of food insecurity 47 and other cardiovascular risk factors (tobacco use, obesity, diabetes) in these regions. 48 We also found that Black adults had higher mortality rates than their White counterparts in both rural and urban areas of the country. Although absolute rate differences between Black and White adults across urban areas of the country declined during the study period, relative reductions in mortality were most pronounced among White individuals.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…These patterns may be a result of the higher burden of food insecurity 47 and other cardiovascular risk factors (tobacco use, obesity, diabetes) in these regions. 48 We also found that Black adults had higher mortality rates than their White counterparts in both rural and urban areas of the country. Although absolute rate differences between Black and White adults across urban areas of the country declined during the study period, relative reductions in mortality were most pronounced among White individuals.…”
Section: Discussionsupporting
confidence: 54%
“…These patterns may be a result of the higher burden of food insecurity 47 and other cardiovascular risk factors (tobacco use, obesity, diabetes) in these regions. 48…”
Section: Discussionmentioning
confidence: 99%
“…Considering that risk perception is recognized as a modifiable determinant of health-related behaviors ( 40 , 41 ), it is vital to identify subgroups on which to focus to maximize the maintenance of risk perception or improve the level of CVD risk perception through targeted intervention to prevent a decline in the level of risk perception. Our study highlighted that individuals who were older, had a higher monthly income, and had diabetes were more prone to perceive higher CVD risk, which has been confirmed in earlier studies ( 32 , 38 , 42 ). Our study also found that people who perceived better health status were more likely to be in a high-risk perception class, which was inconsistent with the findings in Korean blue-collar workers ( 15 ).…”
Section: Discussionsupporting
confidence: 89%
“…However, our data suggest that this Midwest population has equivalent or greater CVD risk than other, larger population-based cohorts of African Americans, including the Jackson Heart Study. 66 Future studies are warranted to assess the replicability of these findings in other geographic areas (both urban and rural) and the sustainability potential of the FAITH! App within a broader network of national and international faith-based organizations traditionally prioritizing individuals of African descent.…”
Section: Discussionmentioning
confidence: 95%